Pengaruh Environmental, Social, Governance (ESG) Disclosure, Green Innovation, Dan Eco-Efficiency Terhadap Nilai Perusahaan - Andre Rafael; Hexana Sri Lastanti (Ikatan Da'i Indonesia, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure, green innovation, and eco-efficiency on firm value, with firm size as a control variable. The data used in this study are secondary data obtained from annual reports and financial statements of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The sampling technique used is purposive sampling, resulting in a total of 75 samples that met the research criteria during the observation period. The data were analyzed quantitatively using SPSS software through a panel data regression approach. The results of the study indicate that environmental disclosure has a positive effect on firm value. Social disclosure and governance disclosure have a negative effect on firm value. Meanwhile, green innovation and eco-efficiency have no significant effect on firm value. Furthermore, the control variable, firm size, has a positive effect on firm value.